Extrapolation of Valacyclovir Posology to Children Based on Pharmacokinetic Modeling. Issue 12 (December 2015) - Kechagia, Irene Ariadne; Kalantzi, Lida; Dokoumetzidis, Aristides
Abstract : Background: Valacyclovir is a prodrug of acyclovir. Although acyclovir is approved for children in Europe, valacyclovir is not approved, despite being used off-label. The aim of the study was to extrapolate the approved dosages of acyclovir, to valacyclovir dosages, in children using Monte Carlo simulations based on the population pharmacokinetic (PopPK) models of valacyclovir and acyclovir. Methods: Assuming that the recommended dosages of acyclovir are efficacious, a PopPK model of acyclovir was used to perform simulations to determine a critical concentration (Ccrit ) for which a target criterion is fulfilled, ie, 90% of the simulated patients have acyclovir levels above Ccrit for at least half the time. The same was done for a secondary target, drug exposure, determining a critical area under the curve in 24 hours at steady state. Then a PopPK model of valacyclovir was used to determine by simulations, dosage regimens that fulfill the criteria for both targets. This was repeated for various indications and age groups. Results: Indicatively, for the treatment of varicella zoster virus, in ages 2–12 years, Ccrit and critical area under the curve in 24 hours at steady state were found to be 0.39 mg/L and 9.6 mg/L × h, respectively, using the acyclovir approved doses 20 mg/kg 4 times daily. For these breakpoints, a 20 mg/kg, 3 times daily, valacyclovir dose achieves the targets in 97% and 100% of the patients, respectively. We found that some patients receive higher than the ideal doses of acyclovir. Conclusions: Simulations were used to determine the appropriate doses of valacyclovir in children to support a pediatric investigation plan targeting a paediatric-use marketing authorization application in the European Medicines Agency. Abstract : Supplemental Digital Content is available in the text.